Determination of Phytochemicals and Some Elemental Compositions of Watermelon from Sokoto, Nigeria - Ladan, Zubaida Abubakar (Darul Yasin Al Sys, 2024)
Currently, many people are battling with infectious and chronic diseases in the country. More especially, the chronic diseases are associated with the level of ingredients in the food we take in, therefore, the easiest way to remedy our challenges is to monitor levels of chemicals in foods, especially the ones around us at affordable prices. Watermelon is a typical fruit that is conspicuous in the state, and can be a source of important natural chemicals for body health. The objective of this study was to perform a phytochemical and an elemental analysis of water melon grown in Sokoto state, Nigeria. The phytochemicals were determined with appropriate methods and chemicals of analytical grade, and elements are determined using atomic absorption spectroscopy. Regarding phytochemicals, flavonoids, alkaloids, saponins, and steroids were determined. Sodium levels in the seed, pulp, and peel reveals 0.40±0.02 (ppm), 3.0±0.01 (ppm), 2.00±0.01(ppm) respectively; potassium levels in the seed, pulp, and peel reveals, 5.000 ±0.04(ppm), 0.15±0.02 (ppm), 3.00±0.02 (ppm) respectively. Calcium determination shows values 20±1.0 (ppm), 20.0±1.00 (ppm), 20.30±0.3 (ppm) in seed, pulp, and peel respectively; and magnesium levels in seed, pulp, and peel are, 2.20±0.001 (ppm), 6.0±0.01 (ppm), and 0.40±0.03 (ppm) respectively. Iron levels of seed, pulp, and peel of watermelon reveals, 1.01±0.02 (ppm), 0.10±0.01(ppm), 15.00±0.2 (ppm) respectively; and Zinc 15±0.20 (ppm), 20.0±2.0 (ppm), and 10.00±1.05 (ppm) respectively. The watermelon contains significant amount of phytochemicals like flavonoids, alkaloids, saponins, and steroids useful in many purposes such as antimicrobial agents in neutralising the infectious diseases, a burden in the state. Also, the fruit contains useful elements in significant amount like, sodium, potassium, calcium, magnesium, iron, and zinc, that can be used in people that suffers specific nutritional problems.